ANALISIS PENERAPAN KONSEP GOING CONCERN SEBAGAI SARANA PERLINDUNGAN KONSUMEN DALAM PERKARA KEPAILITAN (Studi Putusan Nomor 77/PDT.SUS-PKPU/2020/PN.Niaga.Jkt.Pst) - Maurizka Ananda Putri; Jeane Neltje Saly (Fakultas Hukum Universitas Tarumanagara, 2021)
A business actor's dispute to a consumer arises when the business actor does not give the agreed consumer rights, the business actor does not have good faith and is dishonest to the consumer which causes the consumer to suffer losses. In addition, there is a bankruptcy decision imposed on business actors based on the Law on Bankruptcy and Postponement of Debt Payment Obligation Number 37 of 2004 which makes the business actor (bankrupt debtor) not entitled to his assets, then the assets will be managed by the curator. This situation makes consumers more disadvantaged because consumers are concurrent creditors whose repayments are carried out the last after preferred creditors and separatists. In the settlement of bankruptcy assets, generally confiscation and auction of bankrupt assets are carried out, however the going concern option or business continuity can provide a large portion of the protection of consumer rights which tends to be neglected. Going concern is a term commonly used in the accounting sector related to the financial statements of a company (entity) made by public accountants in a professional manner, in terms of going concern business practice it is used as a parameter in estimating the ability of an entity to maintain its business activities. within a certain period stipulated in Article 104 of the bankruptcy law. By implementing a going concern in bankruptcy, it can guarantee the fulfillment of consumer rights for apartment buyers.